2020
DOI: 10.3389/fpls.2020.560869
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Cultivar, Seed Origin, and Substrate on Bacterial Diversity of the Sugar Beet Rhizosphere and Suppression of Soil-Borne Pathogens

Abstract: The rhizosphere microbiome is crucial for plant health, especially for preventing roots from being infected by soil-borne pathogens. Microbiota-mediated pathogen response in the soil-root interface may hold the key for microbiome-based control strategies of phytopathogens. We studied the pathosystem sugar beet-late sugar beet root rot caused by Rhizoctonia solani in an integrative design of combining in vitro and in vivo (greenhouse and field) trials. We used five different cultivars originating from two propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 67 publications
1
40
0
3
Order By: Relevance
“…Although an influence of the soil on the establishment of the endophytic seed microbiome was reported before [ 70 ], it seems that the genotype represents higher impact on the seed microbiome. Previous studies reported similar results for the rice seed microbiome and the sugar beet seed microbiome showing that the genotype had a higher influence on the seed microbiome than the geographic location [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 53%
“…Although an influence of the soil on the establishment of the endophytic seed microbiome was reported before [ 70 ], it seems that the genotype represents higher impact on the seed microbiome. Previous studies reported similar results for the rice seed microbiome and the sugar beet seed microbiome showing that the genotype had a higher influence on the seed microbiome than the geographic location [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 53%
“…Surprisingly, breeding was shown to cause similar, long-term microbiome shifts as well ( Pérez-Jaramillo et al, 2018 ). In the last centuries, plant breeding was directed to high yields and to resistance toward pathogens; high yield cultivars enriched plant growth promoting microorganisms ( Pérez-Jaramillo et al, 2018 ), while resistant cultivars enrich microorganisms antagonistic toward pathogens ( Adam et al, 2018 ; Mendes et al, 2019 ; Wolfgang et al, 2020 ). For example, Rhizoctonia -tolerant cultivars of sugar beet, mainly mediated by the Fort Collins Resistance (USDA), resulted in an enrichment of bioactive Pseudomonas strains in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rhizoctonia -tolerant cultivars of sugar beet, mainly mediated by the Fort Collins Resistance (USDA), resulted in an enrichment of bioactive Pseudomonas strains in the rhizosphere. Strains of Pseudomonas are also able to induce the same resistance under experimental settings ( Wolfgang et al, 2020 ). Only recently two independent studies have shown that microorganisms can shape their host phenotypes by evoking resistance traits that are undistinguishable from innate plant immunity: in sugar beets two members of the native endorhiza microbiota ( Chitinophaga and Flavobacterium) were shown to confer resistance to the host plant against Rhizoctonia solani ( Carrión et al, 2019 ) and in rice a seed-endophytic Sphingomonas melonis strain was shown to confer disease resistance against Burkholderia plantarii that causes seedling blight ( Matsumoto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed beneficial effects of RBs are relatable to their phytochemical profile, that in turn depends on agronomic and pedoclimatic conditions [19][20][21][22]. Indeed, an high biochemical variability, related to cultivar specificity and geographical origin, has been shown in previous studies [23][24][25], but yet the variability of the RB chemical composition, induced by harvest time and seasonality, has not been deeply investigated. Therefore, the scarce knowledge of a defined metabolic profile of red beetroot could barely help the producer to address its use in terms of a top-quality food for health care.…”
Section: Introductionmentioning
confidence: 99%